Future of Probiotics and Prebiotics and the Implications for Early Career Researchers - Spacova, Irina; Dodiya, Hemraj B.; Happel, Anna-Ursula; Strain, Conall; Vandenheuvel, Dieter; Wang, Xuedan; Reid, Gregor (Frontiers in Microbiology, 2020)
The opportunities in the fields of probiotics and prebiotics to a great degree stem from what we can learn about how they influence the microbiota and interact with the host. We discuss recent insights, cutting-edge technologies and controversial results from the perspective of early career researchers innovating in these areas. This perspective emerged from the 2019 meeting of the International Scientific Association for Probiotics and Prebiotics - Student and Fellows Association (ISAPP-SFA). Probiotic and prebiotic research is being driven by genetic characterization and modification of strains, state-of-the-art in vitro, in vivo and in silico techniques designed to uncover the effects of probiotics and prebiotics on their targets, and metabolomic tools to identify key molecules that mediate benefits on the host. These research tools offer unprecedented insights into the functionality of probiotics and prebiotics in the host ecosystem. Young scientists need to acquire these diverse toolsets, or form inter-connected teams to perform comprehensive experiments and systematic analysis of data. This will be critical to identify microbial structure and co-dependencies at body sites and determine how administered probiotic strains and prebiotic substances influence the host. This and other strategies proposed in this review will pave the way for translating the health benefits observed during research into real-life outcomes. Probiotic strains and prebiotic products can contribute greatly to the amelioration of global issues threatening society. The intent of this article is to provide an early career researcher’s perspective on where the biggest opportunities lie to advance science and impact human health.